Eight weeks of core stability training improves landing kinetics for freestyle skiing aerials athletes - Wei, Ming; Fan, Yongzhao; Lu, Zulei; Niu, Xuesong; Wu, Hao (Frontiers in Physiology, 2022)
Freestyle skiing aerials are characterized by technical elements including strength, flexibility and balance. Core stability in aerials can improve sporting performance. Objective: This study aimed to analyze the effect of 8 weeks of core stability training on core stability performance in aerials. Methods: Participants were randomly assigned to a control group (CG; n = 4male + 5female; age 15.89 ± 1.54 years; height 163.11 ± 6.19 cm; weight 55.33 ± 5.07 Kg) and a training group (TG; n = 4male+5female; age 16.11 ± 2.47 years; height 161.56 ± 5.25 cm; weight 57.56 ± 8.11 Kg). Body shape, the performance of core stability, and landing kinetics were measured after 8 weeks of core stability training. Independent sample t-tests were used to compare baseline values between groups. A two-way repeated-measures analysis of variance (ANOVA) (time × group) was used. Results: The TG improved body shape, and waist circumference (t = −2.333, p = 0.020). Performance of core stability, squat (t = −4.082, p = 0.004), trunk flexion isometric test (t = −4.150, p = 0.003), trunk lateral bending isometric test (t = −2.668, p = 0.008), trunk rotation isometric test (t = −2.666, p = 0.008), side bridge (t = −2.666, p = 0.008), back hyperextension (t = −4.116, p = 0.003), single foot triple jump (t = −4.184, p = 0.003), and single-leg balance with eyes closed (t = 4.167, p = 0.003). Performance in landing kinetics, End/Phase (t = −4.015, p = 0.004), sagittal axes (t = −4.598, p = 0.002), frontal axis (t = 3.116, p = 0.014), peak power hip changing range (t = 2.666, p = 0.017), peak power knee changing range (t = 2.256, p = 0.049). Conclusion: Core stability training leads to improvements in body shape, the performance of core stability, and landing kinetics. Therefore, these improvements can improve the sporting performance in aerials competitions.